The application of a 6% reactor in high-voltage capacitor bank switching - Chiradeja, Pathomthat; Ngaopitakkul, Atthapol (My University, 2016)
The switching of capacitor banks at high voltage for power-factor improvement and voltage support can generate significant transients. Such switching transients are produced by inrush currents and transient overvoltages in systems to which the capacitor bank is connected. These switching transients can cause damage to insulation and mal-operation of protective relays. This paper presents the simulation and investigation of a switching large-shunt capacitor bank in a 230kV Thailand substation system. A computer simulation using PSCAD/EMTDC was performed to determine the peak of the transient currents, the oscillation overvoltage and the frequency of the inrush current. The transient inrush current is generated by energizing of the 4×72 MVAr, 230 kV shunt capacitor banks. Methods of inrush current transient analysis and reduction were evaluated. Limiting the transients with a 6% reactor in series was simulated. The simulations indicate that the 6% reactor can significantly reduce the magnitude of the transients.
Keywords: 6% Reactor; Back-to-back capacitor switching; Current limiting reactor; Inrush current; Shunt capacitor bank; Switching transients